LEXIC-SEMANTIC FEATURES OF APHORISMS SYSTEMS (American Journal of Research in Humanities and Social Sciences, 2024)
This article deal with lexic-semantic features of aphorisms. Linguistic sciences’ opinion are given and semantic categories of aphorisms are discussed.